Rating and anti-rating of rational implementations from Estonian to Ukrainian prisons service - Halai, Andrii; Halai, Viktoriia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
In the article is finalized the results of professional educational visit to the Estonian prisons service. Standing on that analysis authors are making some advices for implementation to Ukrainian legal system.